Self-reported leisure time exercise change during smoking cessation in men and women. (December 2019) - Harrison, Katherine; Noyes, Nicole; Friedrichsen, Samantha; Tosun, Nicole; Oyenuga, Abayomi; Allen, Sharon
Highlights: Leisure-time exercise increased among abstinent participants. Leisure-time exercise did not change among non-abstinent participants. Similar trends in leisure-time exercise were observed among abstinent men and women.